(untitled) (PROSPECTIVE RESEARCHES, 2024)
As a result of gender socialization, women around the world still face significant challenges in their various activities. Empowerment would serve as a platform through which women can combat unequal treatment and realize full control over their lives. Sports and physical activities can serve as a platform for women to achieve this. The aim of this research is to explore the potential of sport and physical activity to empower girls and women in general. To achieve the research objectives, a questionnaire was distributed to female students of the College of Physical Education and Sports Sciences at AL-Mustaqbal University. (45) responses were obtained. The data was analyzed using the advanced statistical program SmartPLS V.4. Further experiences of empowerment as a result of participation in sports and physical activity, and barriers, were explored. Which limits participation in order to recommend further promoting the participation of girls and women in sports and physical activities. The research reached a set of conclusions, the most important of which is that empowering women through sports is a multifaceted journey that goes beyond sporting achievements. It includes personal development, social change and gender equality. After a comprehensive study of this topic, a set of recommendations can be presented, the most important of which is that empowering women through sports requires commitment, cooperation, and continuous effort. These recommendations provide a roadmap for stakeholders at all levels to harness the transformative potential of sport in promoting gender equality and women's empowerment.